2022
DOI: 10.3390/molecules27061892
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals of Avocado Residues as Potential Acetylcholinesterase Inhibitors, Antioxidants, and Neuroprotective Agents

Abstract: Avocado (Persea americana) is a widely consumed fruit and a rich source of nutrients and phytochemicals. Its industrial processing generates peels and seeds which represent 30% of the fruit. Environmental issues related to these wastes are rapidly increasing and likely to double, according to expected avocado production. Therefore, this work aimed to evaluate the potential of hexane and ethanolic peel (PEL-H, PEL-ET) and seed (SED-H, SED-ET) extracts from avocado as sources of neuroprotective compounds. Minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…It has been observed that oleic acid binds to different allostatic sites of enzyme by interaction to OH and NH 3 functional groups at cystine 319 and tyrosine 320 and show some non-competitive reversible inhibition [ 53 ]. The literature suggests that various plant extracts containing smaller amounts of oleic acid have shown promising anti-cholinesterase effects [ 54 , 55 ]. However, the major effect has been observed against BChE in many cases.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that oleic acid binds to different allostatic sites of enzyme by interaction to OH and NH 3 functional groups at cystine 319 and tyrosine 320 and show some non-competitive reversible inhibition [ 53 ]. The literature suggests that various plant extracts containing smaller amounts of oleic acid have shown promising anti-cholinesterase effects [ 54 , 55 ]. However, the major effect has been observed against BChE in many cases.…”
Section: Resultsmentioning
confidence: 99%
“…Catechin was reported to be the most promising anti-AD compound for its low binding energy for AChE [ 88 ]. Then, other reports of AChE inhibitory activity where the catechin content was high enough could be also explained [ 67 , 78 , 83 ]. Ben Rejeb et al (2020) stated that extracts from artichoke by-products (leaves, bracts and stems) inhibited AChE and BChE activity, and they related this to the presence of flavonoids in a positive and significant way [ 93 ].…”
Section: Phenolic Compounds From Fruit and Vegetable By-products: Neu...mentioning
confidence: 92%
“…An alternative to reduce the amount of unexploited waste with a negative impact on the environment is represented by their valorisation through green extraction, isolation and purification of bioactive compounds in order to obtain added value products, useful in the prevention and treatment of various maladies. Numerous studies have shown that vegetable waste is an important and low-cost source of primary and secondary metabolites with medicinal and nutritional value, such as phenolic compounds (phenolic acids [20,38,67,76], flavonoids [14,18,20,22,23,34,42,56,65,71,74], anthocyanins [20,21,35,57,71], vitamins (vitamin A [25], vitamin E [21], vitamin D [25], vitamin C [21,25,65,74], amino acids [25], alkaloids [11,18], glucosinolates [23], fatty acids [21], poly-saccharides [55], terpenes [14,38,57,74].…”
Section: Current Strategies For Vegetal Waste Valorisationmentioning
confidence: 99%